HISTORICAL RETROSPECT: ENVIRONMENT POLLUTION, INDUSTRIAL POLLUTION (International Journal of Food and Nutritional Sciences, 2022)
Despite all the legal provisions, historically the statutory authorities have miserably failed tocontrol the water pollution. How to bring down the extent of pollution to a desired level? This isreally a problem. Especially when looked in the socio-economic spectrum. Our country is adeveloping country. We need industries to cater to the needs of our people, to enhance theirstandard of living and at the same time to compete with the advanced nations in the worldmarket. The center of problem is of harmonization of pollution with industries.